Aplikasi Pembelajaran Kosa Kata Untuk Anak Berkebutuhan Khusus Tunarungu Menggunakan Metode Algoritma Fisher-Yates - Aggry Saputra; Zulfachmi Zulfachmi; Agung Alviandi (Prosiding, 2023)
Deafness is a type of special need that is of concern to the government in terms of equality in obtaining education as stated in Law of the Republic of Indonesia No. 20 of 2003 concerning National Education Chapter IV Article 5 paragraph (1) states that "Every citizen has the same right to obtain quality education" and paragraph (2) "Citizens who have physical, emotional, mental, intellectual and /or social rights to obtain special education”. The problem faced by deaf student is the difficulty of capturing the information conveyed by the teacher during the learning process. These limitations make it difficult for deaf children to master good and correct vocabulary. The aim of this research is to help student with special needs learn vocabulary through learning media. With this application, it is hoped that it can meet the vocabulary learning needs, especially for Deaf SMPLB students at SLB Karya Mandiri Kijang.